A serial mediation model of patient safety climate on nurses' compliance with standard precautions: the roles of infection prevention climate and attitude - Jiang, Wenjing; Cao, Li; Liu, Qiurun; Zhou, Ping; Dai, Anna; Liao, Xiaoyu; Tang, Juan (Frontiers in Public Health, 2025)
ObjectivesThis study tested a serial mediation model, based on Social Cognitive Theory (SCT), to explore how patient safety climate is associated with nurses' compliance via infection prevention climate (IPC) and standard precautions attitude.MethodsA cross-sectional survey was conducted among 913 registered nurses from 34 hospitals in China using validated instruments. Data were analyzed using PROCESS macro (Model 6) with 5,000 bootstrap samples, adjusting for age, gender, education, professional title, hospital level, and infection control training frequency.ResultsPatient safety climate had a significant total effect on compliance (βPSC → COMP(total) = 0.551, p < 0.001), but the direct effect became non-significant after including mediators (βPSC → COMP = −0.034, p = 0.378), indicating full mediation. This suggests that patient safety climate was not directly associated with compliance but exerted its influence entirely through infection prevention climate and attitudes, highlighting an indirect yet substantial pathway. All three indirect paths were significant: via infection prevention climate alone (βPSC → IPC → COMP = 0.138), via attitude alone (βPSC → ATT → COMP = 0.102), and via both in sequence [βPSC → IPC → ATT → COMP = 0.346, 95% CI (0.272, 0.426)], with the sequential pathway explaining 59.0% of the total indirect effect. In practical terms, attitude showed the strongest predictive power, with a standardized coefficient of βATT → COMP = 0.666, indicating a clinically meaningful impact on compliance behavior.ConclusionPatient safety climate indirectly enhances compliance through departmental climate and individual attitudes. Interventions targeting both organizational climate and individual beliefs may strengthen compliance with standard precautions in clinical practice.